PERIODE PEMBUNGAAN DAN PEMBUAHAN NYAMPLUNG (Calophyllum inophyllum) PADA TEGAKAN BENIH PROVENAN DI WONOGIRI - Eritrina Windyarini; Tri Maria Hasna; Hamdan Adma Adinugraha; Budi Leksono (Jurnal Pemuliaan Tanaman Hutan, 2020)
Nyamplung (Calophyllum inophyllum) is a potential type of non-timber forest product (NTFP) with high oil yield which is useful as an alternative renewable energy sources and herbal medicine-cosmetics. Result of population selection level in Java Island have been used to build Provenan Seed Stand (PSS) nyamplung in KHDTK Wonogiri (Central Java) as an improved seed source with high oil yield and fruit productivity. Seed become nyamplung part that is used as oil raw material which is strongly influenced by flowering and fruiting period. Information on flowering fruiting ability and period is needed to support the availability of raw materials in a sustainable supply for the nyamplung oil industry. Seed become nyamplung part that is used as oil raw material which is strongly influenced by flowering and fruiting period. Information on flowering fruiting ability and period is needed to support the availability of raw materials in a sustainable supply for the nyamplung oil industry. Observation of flowering and fruiting period focused on 465 individual trees in nyamplung PSS at KHDTK Wonogiri through monthly monitoring by calculated flowering fruiting individualtree during 5 years (2014-2018). The results showed that the flowering period of nyamplung in TBP Wonogiri varied during 2014-2018. Flowering and fruiting occurs almost throughout the year. However, the peak of flowering and fruiting occurs mostly in March-August (end of the rainy season to the middle of dry season). In general, the trend of flowering and fertilization increased in 2014-2016, then decreased in 2017-2018, which is thought to be influenced by the higher canopy density. The environmental factor that most influences flowering is number of rainy days, while fertilization of TBP was strongly influenced by temperature. The management of TBP require future action such: second thinning, top pruning, application of fertilizers and hormones to stimulate flowering, and further detailed observations of flowering fruiting stage and its interaction with microclimate.